JENIS TUMBUHAN ASING INVASIF YANG MENGANCAM EKOSISTEM DI TAMAN NASIONAL GUNUNG GEDE PANGRANGO, RESORT BODOGOL, JAWA BARAT - Sunaryo; Tahan Uji; Eka Fatmawati Tihurua (The East Java Biological Society, 2012)
Study on invasive alien species was conducted in Gunung Gede Pangrango National Park, Bodogol Resort. Vegetation analyses in two different heights location was carried out by making of plots. First location was established at 700 m a.s.l., while second site was located at 800 m a.s.l., with 0.14 ha each plot. The result showed 10 trees species of 7 families and 29 saplings species of 14 families was found in the fi rst plot, whereas 12 trees species of 10 families and 48 saplings species of 28 families was located in the second plot. Three invasive species which threatened ecosystem in this study region were Maesopsis eminii, Calliandra calothyrsus and Austroeupatorium inulifolium.